Fawāid Al-Hadzfi Wa Al-Taqdīr Fī Sūrah Al Baqarah - Saepul Rizal Mahdi; Budiansyah (Mauriduna: Journal of Islamic Studies, 2023)
إن من صور إعجاز القرآن أنه نزل بالأساليب البلاغية، ويعتبر الحذف والتقدير من أساليب اللغة العربية التي اعتمد عليها القرآن من أجل الحصول على المعاني الغزيرة والفصاحة. وتهدف هذه الدراسة إلى استخراج مواضع الحذف والتقدير وكشف فوائدهما. ولتحقيق هذا الهدف اختار الباحث المنهج الوصفي التحليلي، واستعان الباحث في دراسته بعملية استقراء الآيات وتحليلها. وتوصل الباحث إلى نتائج من أبرزها: أولا: أثبتت هذه الدراسة وجود الحذف والتقدير في سورة البقرة، ثانيا: وردت في سورة البقرة الفوائد البلاغية للحذف وهي ما حذف اختصارا ودل عليه المقام، ومنها ما حذف للعلم به أو لاحتقاره أو لشناعة ذكره، ومنها ما حذف للاستهزاء أو للتعظيم Asālīb hadzf and taqdīr are two of the most often utilized usluub (ways/variants) in the Qur'an to communicate meaning, among the miraculous forms of the Qur'an, namely descending with numerous variations and methods (asālīb) in the verses. This study intends to examine the meaning conveyed in uslūb hadzf and taqdīr in surah al-baqarah, as well as their impact on understanding the semantics of Qur'an verses. The researcher employs a descriptive-analytical method to achieve the research objectives; in this study, the researcher employs one of the scientific observation tools, namely researching and analyzing Qur'anic verses that contain uslūb hadzf and taqdīr and explaining the meaning of balaghahthe verse. And the results of the research are as follows : The surah al-baqarah contains uslūb hadzf and taqdīr, according to this study, and The contextual connotations of uslūb hadfz and taqdīr serve a variety of purposes, including abbreviating phrases that have been comprehended from a speech contest or degrading or honoring it, and Something that is erased offers good benefits and wisdom that humans are aware of or are unaware of. Diantara bentuk mukjizat al-Qur’an yaitu turun dengan berbagai variasi bahasa arab pada ayat-ayatnya. Asālīb hadzf dan taqdīr merupakan salah satu usluub (metode/variasi) yang paling banyak digunakan dalam Al-qur’an untuk memberikan makna-makna yang lebih dalam dan sempurna. Penelitian ini bertujuan untuk mencari letak uslūb hadzf dan taqdīr pada surah Al-Baqarah, dan menganalisis makna yang tersirat pada uslūb tersebut, serta pengaruhnya dalam memahami semantik ayat-ayat al-qur’an. Untuk mencapai tujuan penelitian tersebut, peneliti menggunakan metode deskriptif. Peneliti meneliti dan menganalisis ayat-ayat yang di dalamnya mengandung uslūb hadzf dan taqdīr serta menjelaskan makna balaghah yg tersirat dalam ayat-ayat tersebut. Adapun diantara hasil penelitian ini ialah: terbukti bahwa dalam surah al-baqarah terdapat uslūb hadzf dan taqdīr. dengan fungsi yang beragam, diantara untuk menyingkat perkataan yg telah di pahami dari konteks, atau untuk merendahkan hal yg dihapus, atau mengagungkannya, atau Sesuatu yg di hapus tersebut memiliki faidah dan hikmah baik di ketahui atau belum di ketahui oleh manusia.